Promoting efficient retail payments in Europe - Iftekhar Hasan; Emmi Martikainen; Tuomas Takalo (Bank of Finland, 2014)
In this article we first document the evidence showing how an efficient retail payment infrastructure enhances economic performance. We then review the policy tools available to promote efficient retail payments in Europe. We argue that while SEPA is an important policy initiative that harmonizes payment methods across the EU, it alone is not enough. Vigorous competition and consumer protection policies as well as direct interventions discouraging large value cash payments would be particularly attractive policy tools as they would put no strain on stretched government budgets.
URN:NBN:fi:bof-201410243026
Keywords: G21; G28; 330; Retail payment; SEPA; competition; consumer protection; economic performance